Prevalence and Risk factors for Opisthorchiasis in Tha Uthen District, Nakhon Phanom Province, Thailand - นครังสุ ขนิษฐา; ช่วงไชยยะ ศรีวิภา; พัดไธสง วีรวัฒน์ (Journal of Health Science of Thailand, 2024)
Opisthorchis viverrini causes a major health problem especially in the northeast and north of Thailand. O. viverrini is a major caused of cholangiocarcinoma. The objective of this study was to investigate the prevalence of O. viverrini infections and factor related to the infection. A cross-sectional study was conducted between January and March 2023 in Phanom sub-district, Tha Uthen district, Nakhon Phanom province, Thailand. Total 293 stool samples were collected using Kato’s thick smear technique to determine the prevalence of helmiths infections; and a set of questionnaire was used to collecte the factors correlating with O. viverrini infection. The overall prevalence of intestinal helminthes infection were 13.0%, of which the prevalence of O. viverrini and mixed O. viverrini and Taenia spp. was 12.6% and 0.4%, respectively. Factors significantly related to opisthorchiasis included having history of parasitic examination (AOR=6.03, 95% CI: 1.41-25.75), eating raw fish (AOR = 5.56, 95% CI: 2.26-13.10) and alcohol consumption (AOR=6.27, 95% CI: 1.32-29.70), (p<0.05); which were positively associated with the infection. The results suggested that O. viverrini infection is still significantly endemic in rural community. Therefore, intervention programs should be implemented in this area.